Comportamento dinâmico e mecânico do solo sob níveis diferenciados de escarificação e compactação - Rosa, David Peres da (2007)
Soil compaction under no-tillage system has been causing serious problems to plant growth and to agriculture machines operation due to high soil resistance to tillage. Soil chiseling is a possible solution, however, some aspects regarding permanence in time, effects on soil mechanical properties and relation to draught required by mobilization mechanisms are not clearly known. In this context, the aim of this work was to evaluate the chiseling and compaction effects on soil mechanical properties under no tillage, as well as their effects on force dynamics on mobilization mechanisms. Two studies were carried out. The first was in a clay texture soil, where the temporal effect of chiseling, traffic and their influences in compressibility, shear of soil, mobilized area and draught required by the planter s shaft of no-tillage seeder, were evaluated. The second study was carried out in sandy loam soil, where the compaction influence on soil penetration resistance, mobilized area, volume, specific operational resistance and draught on a chisel plow, were evaluated. In the first study, chiseling had direct influence on shear resistance, pre-consolidation stress, compression coefficient and draught, and its effect lasted for more than 2 years, but less than 4 years. In the second study, soil compaction increased the penetration resistance, draught and microporosity, and decreased the macroporosity and the mobilized area. The specific operational resistance was higher in soils under induced compaction than without it. The chiseling effect was found in upper layer compared to the chiseled one.